Peran Birokrasi dalam PenempatanTenaga Kerja Indonesia (TKI) di Luar Negeri - Faisal Rani (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2012)
The goal of this observation is to discuss the problem of bureaucrat’s role in protectingimmigrant labor that is sent to the foreign country. The problem of Immigrant labor becomesunsolved problem. This problem becomes the attention of all sides from pre-departure, departureuntil arrival in the country where they work. Bureaucrat through the place of bureaucracy hasimportant role in solving this problem. In this writing, the writer wants to suggest the idea aboutthe role of bureaucracy for protecting Immigrant labor in the foreign country.